The Concept of Sustainable Children Education in Qur’an Perspective - Titin Nurhidayati; M. Nafiur Rofiq; Mar'atus Sholihah (Faculty of Education and Teacher Training of UINSI Samarinda, 2021)
The innate potential that is possessed by humans from birth is the main potential for humans. Humans such as Khalifatu Fi al-Ard have more intelligence potential than other creatures with the main purpose is to be educated properly and sustainably so that their potential can be developed maximumly. This research aims to describe the process of forming human potential through education starting from the prenatal period to postnatal period. The research method of this study is library research with the efforts to search literature references related to the subject that matters on the discussion problems. The study was done with critical and detailed study from literature which are related. The research results indicate that education for children must be done through well prepared plans and aspired by both parents. This process starts from searching for a life partner until children's birth according to the Qur'an guidance. Those processes that are implemented will surely shape children's strong character in education environments, both in an informal or in a formal one.